2021
DOI: 10.1016/j.ultsonch.2021.105855
|View full text |Cite
|
Sign up to set email alerts
|

Application of multi-frequency power ultrasound in selected food processing using large-scale reactors: A review

Abstract: Ultrasound as an eco-friendly green technology has been widely studied in food processing. Nevertheless, there is a lack of publications regarding the application of ultrasound in food processing using large-scale reactors. In this paper, the mechanisms and the devices of multi-frequency power ultrasound (MFPU) are described. Moreover, the MFPU applied in enzymolysis of protein, and washing of fruits and vegetables are reviewed. The application of MFPU can improve the enzymolysis of protein through modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 124 publications
0
46
0
Order By: Relevance
“…However, the use of ultrasound has been reported to permit agitation even inside the biocatalyst particles. [343][344][345][346][347][348] When the mass transfer is slower than the reaction rate, substrate and product concentration gradients are developed inside the biocatalyst particle, resulting in the enzyme located in the core of the biocatalyst particle catalyzing the reaction under conditions far from the ones set and monitored in the liquid phase (Fig. 9A).…”
Section: Generation Of Mass Transfer Resistances and Internal Diffusi...mentioning
confidence: 99%
“…However, the use of ultrasound has been reported to permit agitation even inside the biocatalyst particles. [343][344][345][346][347][348] When the mass transfer is slower than the reaction rate, substrate and product concentration gradients are developed inside the biocatalyst particle, resulting in the enzyme located in the core of the biocatalyst particle catalyzing the reaction under conditions far from the ones set and monitored in the liquid phase (Fig. 9A).…”
Section: Generation Of Mass Transfer Resistances and Internal Diffusi...mentioning
confidence: 99%
“…For example, Ma et al [28] found that dual-frequency osmosonication (40/80 kHz) improved water loss and solid gain and led to higher preservation of phenolic compounds and antioxidant activity than the mono-frequency treatments (40 kHz and 80 kHz). Besides, in previous studies, the multi-frequency power ultrasound has been proven to have great effects in food processing, such as extraction [29] , freezing [30] , drying [25] , [31] , thawing [32] , enzymolysis of protein [33] , [34] , modification of starch [35] , inactivation of enzymes [36] , [37] , as well as cleaning [38] , [39] .…”
Section: Introductionmentioning
confidence: 99%
“…3 ), whose essence is the cycle of growth and contraction of preexisting microbubbles and their collapse in the liquid medium under the ultrasonic field [23] . According to whether the cavitation bubble ruptures or not, the cavitation status can be divided into stable cavitation and transient cavitation [24] . The role of food proteins modification was mainly attributed to the transient cavitation of HIU due to the cavitation bubble will expand rapidly at high acoustic pressure and collapse when it reaches the critical point of resonance, which can generate instantaneous high temperature of up to 5000 K and high pressure of up to 30 MPa in the local area, and then induce a series of physical, chemical, and thermal effects [22] , [25] , [26] , [27] .…”
Section: Acoustic Cavitation Effects Of Hiumentioning
confidence: 99%
“…Based on the above defects, the development of multi-mode HIU equipment for modifying proteins began to rise in recent years. For example, our research team developed 12 kinds of HIU working mode, including sweeping frequency and fixed frequency, multi-frequency and single frequency, multi-frequency with sequential and simultaneous mode, pulse and continuous, contact and non-contact, reflux circulation and optional flow [24] . The four main multi-mode HIU devices for proteins modification were presented in Fig.…”
Section: Innovations Of Hiu Equipment For Modifying Proteinsmentioning
confidence: 99%
See 1 more Smart Citation